Advanced Research in Materials and Engineering Applications - Sidik, Nor Azwadi Che; Samion, Syahrullail (Applied mechanics and materials, 2015)
Collection of selected, peer reviewed papers from the World Virtual Conference on Advanced Research in Materials and Engineering Applications, September 22-26, 2014, Kuala Lumpur, Malaysia. The 196 papers are grouped as follows: Chapter 1: Material Science; Chapter 2: Thermo, Fluid and Flow Research; Chapter 3: Applied Mechanics, Mathematical Modelling, Algorithms, Numerical Methods and Simulation; Chapter 4: Power and Energy Applications, Electrical Research; Chapter 5: Detection, Measurement, Instrumentation, Assessment.